Understanding International Students from Asia in American Universities: Learning and Living Globalization - Tshibaka, Ahoefa S. (Journal of International Students, 2018)
In this book, the editors suggest that the intensity of globalization is helping to reshape the American Education System. The reshaping of the American educational system is reflected in the number of students the United States accommodates from different parts of the world. With an international student count of 1.09 million; the United States is one of the primary destinations for international students in the world. Interestingly, Chinese, Indian, and South Korean students represent more than half (51%) of the overall number of international students in the United States. However, Asian students combined represent 64.3% of the overall number of international students in America, making them the dominant group of students (Ma & Garcia-Murillo, 2018, p. 1).